2022
DOI: 10.1021/acscatal.2c01970
|View full text |Cite
|
Sign up to set email alerts
|

Design and Application of a Screening Set for Monophosphine Ligands in Cross-Coupling

Abstract: In reaction discovery, the search space of discrete reaction parameters such as catalyst structure is often not explored systematically. We have developed a tool set to aid the search of optimal catalysts in the context of phosphine ligands. A virtual library, kraken, which is representative of the monodentate P­(III)-ligand chemical space, was utilized as the basis to represent the discrete ligands as continuous variables. Using dimensionality reduction and clustering techniques, we suggested a Phosphine Opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…Ligand parametrization for predicting the outcome of a catalytic reaction with the help of data science is emerging as a new tool in organic synthesis. Although the Tolman cone angle , descriptor has been of great value in understanding and predicting ligand properties in catalysis, it suffers from certain drawbacks, one of which is not taking ligand flexibility into consideration. Recently, the groups of Sigman and Doyle reported that the use of a single descriptor, minimum percent buried volume or % V bur (min), could nicely predict the ligation state of the catalytically active complexes in both Pd- and Ni-catalyzed reactions . Initially, the authors were inspired by the high efficiency of the DinoPhos ligand family (TyrannoPhos and TriceraPhos) in the Ni-catalyzed coupling reaction of acetal and boroxine (Scheme ).…”
Section: Role Of the Ligands In Forming The L1pd(0) Precatalyst In Situmentioning
confidence: 99%
“…Ligand parametrization for predicting the outcome of a catalytic reaction with the help of data science is emerging as a new tool in organic synthesis. Although the Tolman cone angle , descriptor has been of great value in understanding and predicting ligand properties in catalysis, it suffers from certain drawbacks, one of which is not taking ligand flexibility into consideration. Recently, the groups of Sigman and Doyle reported that the use of a single descriptor, minimum percent buried volume or % V bur (min), could nicely predict the ligation state of the catalytically active complexes in both Pd- and Ni-catalyzed reactions . Initially, the authors were inspired by the high efficiency of the DinoPhos ligand family (TyrannoPhos and TriceraPhos) in the Ni-catalyzed coupling reaction of acetal and boroxine (Scheme ).…”
Section: Role Of the Ligands In Forming The L1pd(0) Precatalyst In Situmentioning
confidence: 99%
“…As showcased below, the designer maps can be applied to various downstream data science steps in multi-objective optimization campaigns. In addition to the reaction optimization applications presented (vide infra), it can be envisioned that this calculated parameter library and chemical space map could be used for many other potential applications such as training set design, novel ligand generation, and mechanistic understanding …”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, heteroaryl tosylate coupling at room temperature without any reduction in the product yield was also demonstrated. Recently, Sigman used the Pd 2 (dba) 3 / CM-phos catalyst system for the SMC of aryl chlorides, aryl triflates, and sterically hindered aryl bromides …”
Section: Cm-phos-type Monophosphorus Ligandsmentioning
confidence: 99%
“…Recently, Sigman used the Pd 2 (dba) 3 /CM-phos catalyst system for the SMC of aryl chlorides, aryl triflates, and sterically hindered aryl bromides. 15 In addition to arylboronic acids, other boronic acid surrogates such as trifluoroborate salts and pinacol boronate esters were coupled smoothly with good yields. 13,14 The coupling of aryl mesylates with potassium (hetero)aryl-, alkyl-, and vinyl-trifluoroborate salts was also successfully accom-plished (Scheme 5B).…”
Section: Suzuki−miyaura Couplingmentioning
confidence: 99%